1968
DOI: 10.2307/2406878
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Competition in Rice. III. The Mechanism of Competition Among Phenotypes

Abstract: The previous papers in this series (Jennings and de Jesus, Jr., 1968;Jennings and Herrera, 1968) concerned the magnitude and direction of interphenotypic competition in varietal mixtures and hybrid populations of contrasting plant types of rice (Oryza sativa L.). Relative yielding ability of the components of the mixtures was established from long-term yield trials of material grown in pure stand. It was concluded that competitive ability and agronomic worth were negatively associated in the materials studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
71
1

Year Published

1972
1972
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 16 publications
(31 reference statements)
10
71
1
Order By: Relevance
“…However, it has also been noted that at Davis, California the trend in CCII population has been towards an increase of seed weight (SUNESON et al ., 1963) . Plant height which affects the position of leaves of a plant relative to that of its neighbours may govern the outcome of competition for light (DONALD, 1963 ;JEN-NINGS & AQUINO, 1968 ;HAMBLIN & DONALD, 1974 (HAMBLIN& DONALD, 1974), rice (JENNINGS & AQUINO, 1968) and soybean (MUMAW & WEBER, 1957) that the strong competitors were taller than the weak ones .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has also been noted that at Davis, California the trend in CCII population has been towards an increase of seed weight (SUNESON et al ., 1963) . Plant height which affects the position of leaves of a plant relative to that of its neighbours may govern the outcome of competition for light (DONALD, 1963 ;JEN-NINGS & AQUINO, 1968 ;HAMBLIN & DONALD, 1974 (HAMBLIN& DONALD, 1974), rice (JENNINGS & AQUINO, 1968) and soybean (MUMAW & WEBER, 1957) that the strong competitors were taller than the weak ones .…”
Section: Resultsmentioning
confidence: 99%
“…It is generally indicated that survival in a mixture is related to adaptability and not necessarily related to yielding ability in pure stands . It also appears that highly competitive plants are tall, leafy and have many tillers with spreading plant type and vigorous vegetative growth (JENNINGS & AQUINO, 1968 ;JENNINGS & HERRERA, 1968) . This is a contrary to the high yielding ideotype suggested by a number of people, which is short with narrow, erect leaves and fewer tillers (THORNE, 1966 ;TANNER et al ., 1966 ;AUGUS et al ., 1972 ;DONALD, 1968) .…”
Section: Resultsmentioning
confidence: 99%
“…HAMBLIN AND C. M. DONALD between the seasons -that is to say, that there was a significant genotype x season interaction and that the influence of neighbours was a minor contributor to the relationships recorded. We accept that this is a possibility but we are not attracted to it for several reasons : first all evidence from other plant communities shows that taller, more leafy plants have a clear competitive advantage in mixed stands (CLEMENTS et al, 1929 and many others), but that they have an unfavourable light profile for growth in monoculture compared with erect-leaved genotypes (HAYASHI & ITO, 1962;JENNINGS & AQUINO, 1968;TANNER et al, 1966;PENDLETON et al, 1968). Secondly the contrast in behaviour in mixed and pure stands was accentuated by the higher nitrogen level, as would be expected from an intensification of the competition for other factors, such as light and water; and, thirdly (and quite subjectively) we believe that the interpretation based on different competitive relationships accords with theoretical probability (DONALD, 1968).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of barley it specifically indicates the height of the ear and the flag leaf during the grain filling period. Leaf length, both because it relates to leaf area and because it influences the bending moment and leaf angle, largely determines the penetration of the leaf into neighbouring foliage (JENNINGS & AQUINO, 1968) and the degree of shading it will impose on other leaves in the canopy. Height and leaf length were therefore used as a measure of the potential of each plant to compete against its neighbours for light.…”
Section: Introductionmentioning
confidence: 99%
“…(MUMAW & WEBER, 1957), rice (Oryza sativa L.) (JENNINGS & DE JESUS., JR., 1968) and barley (SUNESON, 1949;SUNESON & WIEBE, 1942), survival in mixtures was unrelated to yielding ability. After many generations of bulking, cultivars of rice with a tall, late growth habit increased in proportion to other cultivars (JENNINGS & AQUINO, 1968 ;JENNINGS & HERRERA, 1968). Studies of competition in segregating wheat populations show that, in spite of natural selection against short plants, bulk-populations were useful sources for selection of high-yielding lines (KHALIFA & QUALSET, 1975).…”
Section: Introductionmentioning
confidence: 99%